E-Learning and the purpose of maintaining the mind in Islam and its impact on teaching and learning - Yousef A. Baker, El-Ebiary; Ragab Aboumelih, Mohamed Soliman; Ahmed Ramadan, Mohamed Ahmed (The Mattingley Publishing Co., Inc., 2020)
With the spread of modern means of communication, the concept of Electronic Learning (E-Learning) spread, which means: education using modern means of communication, from a computer, the Internet, and media, such as: sound, image, and video, whether in the classroom, or distance education, with less time and effort. And the biggest benefit, and in many cases the e-learning is in an environment far from the teacher, which gave more opportunity to more people to receive the education with easiest way, as well as its role in learning procedures and the purpose of keeping the mind in Islamic law, and how it affects the purposes of the overall law, religion, soul and offspring on the one hand, and also deals with the effect of mind keeping in teaching and learning on the other hand, and this research has discussed the definition The purposes of Islamic law, the definition of the mind, and the care of Islamic law in the mind through the Holy Qur’an and the cleansed Sunnah, and also included the effect of mind keeping on teaching and learning, and the research reached several important results and some recommendations that include the role of developing the educational process how to use the Internet with suspicion Optimization in their implementation procedures.